The mTORC2 Component Rictor Is Required for Load‐Induced Bone Formation in Late‐Stage Skeletal Cells. (18th June 2020) - Lewis, Karl J; Yi, Xin; Wright, Christian S; Pemberton, Emily Z; Bullock, Whitney A; Thompson, William R; Robling, Alexander G
ABSTRACT: Bone relies on mechanical cues to build and maintain tissue composition and architecture. Our understanding of bone cell mechanotransduction continues to evolve, with a few key signaling pathways emerging as vital. Wnt/β‐catenin, for example, is essential for proper anabolic response to mechanical stimulation. One key complex that regulates β‐catenin activity is the mammalian target of rapamycin complex 2 (mTORc2). mTORc2 is critical for actin cytoskeletal reorganization, an indispensable component in mechanotransduction in certain cell types. In this study, we probed the impact of the mTORc2 signaling pathway in osteocyte mechanotransduction by conditionally deleting the mTORc2 subunit Rictor in Dmp1‐expressing cells of C57BL/6 mice. Conditional deletion of the Rictor was achieved using the Dmp1–Cre driver to recombine Rictor floxed alleles. Rictor mutants exhibited a decrease in skeletal properties, as measured by DXA, μCT, and mechanical testing, compared with Cre‐negative floxed littermate controls. in vivo axial tibia loading conducted in adult mice revealed a deficiency in the osteogenic response to loading among Rictor mutants. Histological measurements of osteocyte morphology indicated fewer, shorter cell processes in Rictor mutants, which might explain the compromised response to mechanical stimulation. In summary, inhibition of the mTORc2 pathway in late osteoblasts/osteocytes leads to decreased bone mass and mechanically induced bone formation. © 2020 The Authors. JBMR Plus published by Wiley Periodicals, Inc. on behalf of American Society for Bone and Mineral Research.